Nrf2: a potential therapeutic target for naturally occurring anticancer drugs?. (3rd August 2017) - Catanzaro, Elena; Calcabrini, Cinzia; Turrini, Eleonora; Sestili, Piero; Fimognari, Carmela
ABSTRACT: Introduction : Nuclear factor (erythroid-derived-2)-like 2 is one of the most efficient cytoprotective rheostats against exogenous or endogenous oxidative insults. At present, the modulation of the Nrf2 pathway represents an interesting and highly explored strategy in the oncological area. Area covered : In this review, we present and discuss the different modulation of the Nrf2 pathway by some natural compounds with a well demonstrated anticancer activity, and critically analyze the challenges associated with the development of an Nrf2-based anticancer strategy. Expert opinion : Many natural compounds with a well-defined anticancer activity are able to modulate this pathway. Both Nrf2 inducers and inhibitors can be useful as anticancer strategy. However, since Nrf2 modulates many networks potentially involved in the detoxification process of anticancer drugs, its activation in cancer cells could lead to chemoresistance. The switch between a beneficial or detrimental role of Nrf2 in cancer cells essentially depends on the tight control of its activity, the specific conditions of tumor microenvironment, and cell type. In line with the paucity of clear data related to the mechanisms underpinning the role of Nrf2 in cancer development and chemoresistance, discovery and development of Nrf2-based strategies is one of the most critical and challenging assignments for fighting cancers.